Improved synchronization criteria for fractional-order complex-valued neural networks via partial control - Hong-Li Li; Ahmadjan Muhammadhaji; Long Zhang; Haijun Jiang; Zhidong Teng (Advances in Difference Equations, 2020)
Abstract In this article, without dividing a complex-valued neural network into two real-valued subsystems, the global synchronization of fractional-order complex-valued neural networks (FOCVNNs) is investigated by the Lyapunov direct method rather than the real decomposition method. It is worth mentioning that the partial adaptive control and partial linear feedback control schemes are introduced, by constructing suitable Lyapunov functions, some improved synchronization criteria are derived with the help of fractional differential inequalities and L’Hospital rule as well as some complex analysis techniques. Finally, simulation results are given to demonstrate the validity and feasibility of our theoretical analysis.